FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2013-2015) - Uswatun Kasanah, 12.05.52.0207; Suwarti, Titiek (Students Journal of Accounting and Banking, 2017)
This study aims to determine the effect of profitability, operating cash flow, debt to total assets, liquidity to dividend policy on Manufacturing companies listed on the Indonesia Stock Exchange 2013-2015. The population is all Manufacturing companies listed on the Indonesia Stock Exchange 2013-2015. Sampling technique in this research is done by using purposive sampling method. The data obtained were analyzed by using multiple linear regression analysis. Hypothesis testing results can be concluded that profitability does not affect the dividend policy. Operating cash flow affects positively to dividend policy. Debt to total assets has no effect on dividend policy. Liquidity has no effect on dividend policy.Keywords:Â Profitability, Operating Cash Flow, Debt to Total Assets, Liquidity and Dividend Policy